A Review of the Protection of Children from Sexual Offences Act, 2012: Recent Amendments and Implications (Indian Internet Journal of Forensic Medicine and Toxicology, 2024)
The POCSO Act of 2012 stands as a pivotal legal instrument in India's efforts to combat child  sexual abuse. This review article critically examines the Act, with a specific focus on the  amendments made since its inception. The analysis delves into the important points of the Act,  the effects of recent amendments, enforcement strategies, challenges encountered, and the  potential future direction of child protection within this legal framework.
Keywords: POCSO Act; sexual offenses; child protection; amendments; legal framework